Simultaneous Quantification of Multiple Polycyclic Aromatic Hydrocarbons in Aqueous Media using Micelle Assisted White Light Excitation Fluorescence - John Prakash (Nature Portfolio, 2020)
Abstract Qualitative and quantitative display of multiple fluorescent analytes is made simple and reliable in this micelle assisted methodology. The adopted method involves micelle assisted evincing of ppb level of PAHs in water; measurement of total fluorescence (white light excitation fluorescence, WLEF) and data deciphering using multivariate analysis. This protocol yields sensitive and accurate quantification of the cancerous pollutants (PAHs) in aqueous media with Limit of Quantification of the order 1–10 μg/L and accuracy of >98%. The use of WLEF enables the simultaneous acquisition of fluorescence signatures of all the PAHs. It has the additional advantage of being portable, layman-friendly and cost-effective. The optimized amount of surfactants for the simultaneous extraction of PAHs from real samples was estimated as 27.8 mg (19.3 mM) of SDS and 9.1 mg (5 mM) of CTAB. Also, the analytical fidelity of the quantification such as percentage recovery (98 ± 2%), linear dynamic range (2–250 μg/L), RMSEP (<0.5), etc. explains the veracity of methodology.